The Religious and Historical Symbol in Hussein Zidan’s Poetry: Cases from the Collection (Fadha’ li-Mawsim al-Israr) - Abdelaziz, Zineb (LANGUAGE ART, 2024)
The late Algerian poet Hussein Zidan is renowned for his creative and evocative style. Fascinated by symbolism, Zidan’s work allows readers to contemplate and explore, drawing upon their cultural-historical and spiritual-religious knowledge, to independently uncover his intentions and grasp the meaning of his symbolic choices. Studies of Zidan’s works remain scarce, despite their notable spiritual nature and guidance through crucial junctures in the nation’s history. Therefore, we have chosen to examine the occurrence of historical symbolism in his poetic texts. Specifically, we address the following central question: What role does Religious and Historical Symbol play in Hussein Zidan’s poetry? Was its use incidental or fundamental in shaping the structure and meaning of his poems? Following the descriptive methodology with its various mechanisms, we concluded that religious and historical symbolism in Hussein Zidan’s poetry, as evidenced through our selected examples, constituted a fundamental pivotal dimension in textual construction and semantic fluidity, continuously evoking the past and its symbols, whether with optimism, regret, or sorrow, as demanded by the poem’s contextual requirements.